Enforcement of Law of Copyright Infringement and Forgery with the Rise of the Digital Music Industry - Nevey Varida Ariani (Jurnal Penelitian Hukum De Jure, 2021)
The current pandemic situation encourages musicians to be productive in creating digital works such as songs and music so that their creative works can produce moral and economic values. However, infringement and forgery of digital music works are rampant. The issue of royalties is still a problem in the digital music industry in Indonesia, including new challenges to the role of aggregators and Collective Management Organization. The problem of this research is how the enforcement of the law of copyright infringement and forgery is with the emergence of the digital industry. This research used a qualitative method with a normative juridical approach. The results of the research showed that the increasing and complicated law enforcement related to digital music copyright is influenced by regulations such as complaint offense that hindered the law enforcement. The process of coordination and supervision between the Civil Servant Investigator (PPNS) of the Directorate General of Intellectual Property and other law enforcement officers needs to be improved. Law enforcement includes payment of compensation, termination of certain activities that cause harm to creators and owners of related rights, obligation to withdraw from circulation, revocation of business licenses, termination of business activities, and the last resort of ultimum remedium in the form of criminal sanctions. Dissemination of information and knowledge regarding IPR law and its derivative regulations including Government Regulation No. 50 Year 2021 carried out by the government is part of the legal protection of the society to increase public legal awareness in the digital era.